2019
DOI: 10.1371/journal.pone.0212033
|View full text |Cite|
|
Sign up to set email alerts
|

Nine-year distribution pattern of hepatitis C virus (HCV) genotypes in Southern Italy

Abstract: Introduction It has been greatly described that different hepatitis C virus (HCV) genotypes are strictly correlated to various evolution, prognosis and response to therapy during the chronic liver disease. Aim of this study was to outline the changes in the epidemiology of Hepatitis C genotypes in Southern Italy regions from 2006 to 2014. Material/Methods Prevalence of HCV genotypes was analyzed in 535 HCV-RNA positive patients with chronic Hepatitis C infection, select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 51 publications
3
9
0
Order By: Relevance
“…Pakistan is second to Egypt in the list of high prevalence countries of the world for CHC infection with 4.9% prevalence where majority of HCC cases (60-70%) are attributed to HCV infection [16][17][18]. There are several reports aimed to associate HCV genotype with evolution, prognosis and therapy response to chronic liver disease; however, no consensus has yet been established [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Pakistan is second to Egypt in the list of high prevalence countries of the world for CHC infection with 4.9% prevalence where majority of HCC cases (60-70%) are attributed to HCV infection [16][17][18]. There are several reports aimed to associate HCV genotype with evolution, prognosis and therapy response to chronic liver disease; however, no consensus has yet been established [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that HCV is not autochthonous to Latin America, which is supported by the low prevalence of infection in native groups in this region [7]. In Venezuela, HCV genotype distribution has been maintained during the last 20 years (G1 > G2 > G3) and is similar to that reported in other Latin American countries, such as Argentina and Mexico, and in Europe, specifically in southern Italy, with a significantly higher frequency of G2 compared to G3 [1, 13].…”
Section: Discussionmentioning
confidence: 80%
“…This is the case of genotype-1 and genotype-3 associated with an 80% higher risk of HCC [ 4 ]. In line with this observation, HCV genotype-1b, the most prevalent genotype in Italy [ 11 ], showed to have a higher risk of developing HCC [ 2 ].…”
Section: Introductionmentioning
confidence: 84%